Aspects of infection in intensive care unit - prevention and control - Hassan, KA; Hasan, MK; Chowdhury, MG; Akhter, H (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):474-6 The abstract of this article is available on the PubMed website